Systematic approach to assembly system design Designing an assembly system in a low volume, rapid growth scenario - TENFÄLT, AUGUST; Ansgar, Martin (My University, 2018)
Arcam is a company that develops and manufactures additive manufacturing machines for production of metal parts. Production is planned to move to larger facilities, as to facilitate future increases in capacity requirements. There is existing theory on systematic approaches to production system design, which in this thesis has been adapted and applied in designing the mechanical assembly subsystem. Requirements on the assembly system were found to focus on handling uncertainty and gradual changes in product mix and production volumes. Analysis of current product and assembly system characteristics revealed a large work content and a high degree of complexity. A division of work into sequential work stations with a team-based organizational structure was found suitable to satisfy system requirements as well as prioritized metrics. Designing assembly systems is complex, and acquiring sufficient knowledge of preconditions and requirements in a timely manner is difficult. The use of a systematic approach for assembly system design was found to be beneficial, as complexity was reduced and because structuring and planning of design activities was simplified.
Keywords: Produktion; Transport; Grundläggande vetenskaper; Hållbar utveckling; Övrig industriell teknik och ekonomi; Production; Transport; Basic Sciences; Sustainable Development; Other industrial engineering and economics